ANALISIS CAPITAL ASSET PRICING MODEL (CAPM) DALAM MEMPREDIKSI TINGKAT RETURN SAHAM KOMPAS 100 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2017 - Bandawaty, Euis (Kinerja, 2020)
This study is to determine the accuracy of the CAPM model in predicting 100 compass stock returns listed on the Indonesia Stock Exchange for the period 2013-2017. The variables of this study are 100 stock compass returns, Beta, Risk-Free, and Market return. The accuracy of the CAPM model is measured by standard deviation and t-test. The population of this research is all the monthly stock returns of the compass 100 stock index have gone public on the Indonesia Stock Exchange. While the sample used is a monthly stock return of 58 compass 100 companies from 2013 - 2017. The results of this study indicate that the CAPM model is accurate in predicting 100 stock compass returns.